2023
DOI: 10.1001/jamanetworkopen.2023.16930
|View full text |Cite
|
Sign up to set email alerts
|

National Trends in Physical Activity Among Adults in South Korea Before and During the COVID-19 Pandemic, 2009-2021

Abstract: ImportanceThere is a lack of comprehensive data on the association of the COVID-19 pandemic with the prevalence of physical activity in large-scale data sets.ObjectiveTo investigate long-term trends in physical activity using information from a nationally representative survey covering 2009 to 2021.Design, Setting, and ParticipantsThis general population–based and repeated cross-sectional study was conducted from 2009 to 2021 using the Korea Community Health Survey, a nationally representative survey in South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…First, the data utilized by the researchers were missing for people who did not answer all the questions related to the covariates used in this study. The missing data may lead to a biased interpretation of the data as the missing data may have similar factors 4 , 39 . Second, while this study contained data from the pre-pandemic (2014–2019) to the pandemic (2020–2022) period, it did not contain data from the post pandemic (2023–) period 40 .…”
Section: Discussionmentioning
confidence: 99%
“…First, the data utilized by the researchers were missing for people who did not answer all the questions related to the covariates used in this study. The missing data may lead to a biased interpretation of the data as the missing data may have similar factors 4 , 39 . Second, while this study contained data from the pre-pandemic (2014–2019) to the pandemic (2020–2022) period, it did not contain data from the post pandemic (2023–) period 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The data was divided into time periods before and during the COVID-19 pandemic. Since the first case of COVID-19 in South Korea was reported in January 2020, the year 2020 was defined as the first year of the pandemic 21 , 22 . Before COVID-19, 2009–2019, was subdivided into intervals of 2 to 3 years to obtain a stable estimate of the prevalence of allergic diseases (2009 to 2011, 2012–2013, 2014–2015, 2016–2017, and 2018–2019).…”
Section: Methodsmentioning
confidence: 99%
“…In South Korea, a general population-based and repeated cross-sectional study including over 2,7 million Korean adults found that a stable level of physical activity before the onset of the pandemic decreased in 2020 and 2021, particularly among groups of those with increased risk of negative outcomes (older adults, women, urban residents and people with a history of depressive episodes), but also healthy individuals [32]. Interestingly, younger individuals (19-39 years old) showed an initial decrease in their PA prevalence in 2020, but a subsequent increase in 2021, returning to pre-pandemic levels.…”
Section: Walkingmentioning
confidence: 99%